Systemic Air Embolism following CT-Guided Percutaneous Core Needle Biopsy of the Lung: Case Report and Review of the Literature - Marchak, Katherine; Hong, Michael J.; Schramm, Kristofer M. (Seminars in Interventional Radiology, 2019)
Systemic air embolism (SAE) is a rare but serious complication of percutaneous core needle biopsy (PCNB) of the lung. Incidence of clinically apparent SAE is estimated at 0.061%, while clinically silent SAE may be as high as 3.8%. We present the complication of a small SAE during PCNB of the lung in a 78-year-old patient, which resulted in a transient myocardial ischemic event. This case highlights the importance of understanding the mechanism, frequency, and management of rare complications of PCNB of the lung; these complications should be considered in preoperative risk stratification. Regarding evaluation of postbiopsy computed tomography, operators should utilize a systematic search pattern to assess for complications.Level of Evidence: Level 4, Case Report.
Keywords: serious complication; air embolism; lung biopsy; interventional radiology; percutaneous biopsy; CT guided lung biopsy